Financial factors analysis for acquisition premium and anticipation using extreme gradient boosting and deep recurrent neural network - Rayhan, Mohammad; Sultana, Samiha; Majid, Annur (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.